Analisis Komponen RPP Guru Biologi di SMA Negeri Se-Kabupaten Mandailingnatal - Khairunnisa Asnila Lubis; Ely Djulia; Hasruddin Hasruddin (Jurnal Pendidikan Biologi, 2017)
This study aims to analyze the components of Biology Lesson Plan for reproduction system material in public senior high school in Mandailingnatal District. The research method was using quantitative descriptive study with a sample of 20 biology teachers from 14 public senior high schools in Mandailingnatal district. The research instrument used RPP document assessment sheets, observation sheets of instructional implementation and interviews. The results showed that Planning of learning implementation made by biology teacher in public senior high school in Mandailingnatal for reproduction system academic year 2015/2016 was categorized quite well planned with percentage 77%. As a follow-up of the results of this study is expected to teachers to be able to plan better, systematic and operational learning implementation by considering the characteristics of students, include a more appropriate evaluation instrument and more active in cooperation with the MGMP group to produce better learning.